Evaluation of Online-Based Student Learning: Models During New Normal Pandemic Covid-19 in Indonesia - Siswati, Sri; Astiena, Adila Kasni; Savitri, Yolanda (Universitas Negeri Semarang, 2020)
WHO reports that 150 countries have seen 170,000 cases of Covid 19 and 7,000 deaths. Indonesia in June 2020 there were 52,812 cases, 2,720 deaths. The Regional Head adopted a policy of working at home, including West Sumatra and Padang City implementing Large-Scale Social Restrictions (PSBB) in early April, and June 8, 2020 entering the New Normal era. This policy affects formal education that runs online. Webinars on topics related to the Covid-19 outbreak emerged as part of non-formal education. The research objective is to look at the conditions of online formal learning, when the PSBB started and the new normal era. Descriptive research through the Google Form link to students in Padang randomly to obtain information in online learning. Research shows online learning is very helpful in education, but 55.6% of respondents feel less effective during the PSBB and the new normal period increases by 55.7%. Complaints are generally the large number of assignments; the cost is 78.6% burdensome and 98.6% of students are anxious. 80% of students expect e learning or blended learning. At least face-to-face learning is needed for the emotional relationship between students and lecturers in online learning. New strategies and techniques for dealing with blended learning for non-formal education need to be carried out with the discipline of health protocols.